2015
DOI: 10.1002/acp.3171
|View full text |Cite
|
Sign up to set email alerts
|

Learning By Tracing Worked Examples

Abstract: Cognitive load theorists have only recently begun to test the role of the body in learning. Tracing the index finger over the surface of instructions while reading, an embodied pedagogy based on Montessori's sandpaper letters, may hold substantial promise for learning by reducing cognitive load. Two experiments tested whether students who traced their index fingers against paper-based worked example instructions in triangle geometry (Experiment 1; N = 52) and order of operations (Experiment 2; N = 54) would pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 60 publications
(86 reference statements)
2
28
0
Order By: Relevance
“…Given that one of the largest tracing effects observed to date was generated using worked examples on parallel lines angle relationships (Hu et al, 2015, Experiment 1), we chose these materials as a testbed, and in addition recruited a larger sample than typical previous studies to maximize the sensitivity of hypothesis tests. We found in the present study replicates several earlier studies (e.g., Du & Zhang, 2019;Ginns et al, 2016;Hu et al, 2015;Yeo & Tzeng, 2020) finding transfer effects in mathematical domains. From a cognitive load theory perspective, tracing effects on transfer questions are consistent with such actions supporting both initial schema construction and subsequent automation (Cooper & Sweller, 1987).…”
Section: Acquisition Phasesupporting
confidence: 93%
“…Given that one of the largest tracing effects observed to date was generated using worked examples on parallel lines angle relationships (Hu et al, 2015, Experiment 1), we chose these materials as a testbed, and in addition recruited a larger sample than typical previous studies to maximize the sensitivity of hypothesis tests. We found in the present study replicates several earlier studies (e.g., Du & Zhang, 2019;Ginns et al, 2016;Hu et al, 2015;Yeo & Tzeng, 2020) finding transfer effects in mathematical domains. From a cognitive load theory perspective, tracing effects on transfer questions are consistent with such actions supporting both initial schema construction and subsequent automation (Cooper & Sweller, 1987).…”
Section: Acquisition Phasesupporting
confidence: 93%
“…Several studies support the idea that performing tracing activities with fingers and other simple hand movements can aid learners (e.g. Agostinho et al, 2015 ; Brooks & Goldin-Meadow, 2016 ; Dubé & McEwen, 2015 ; Ginns, Hu, Byrne, & Bobis, 2016 ; Hu, Ginns, & Bobis, 2015 ; Ouwehand, van Gog, & Paas, 2016 ). Results such as these can be taken as evidence for the claim that even very minor changes in interaction design towards bodily engagement can affect learning performance (see Schwartz & Plass, 2014 , for a similar conclusion).…”
Section: Reviewmentioning
confidence: 86%
“…Similar to gestures, such coordinated muscular movements can be considered examples of embodied cognition, resulting in memory traces that make an additional contribution to the mental representation of the phenomenon or concept explored (Pouw et al 2014). Accordingly, research on finger tracing has demonstrated that learners benefit from tracing a certain shape (for example, temperature curves or the water cycle) with the index finger (Agostinho et al 2015;Ginns et al 2016;Tang et al 2019). According to Fiorella and Mayer (2016), tracing can be considered to be one example of learning by enacting, meaning that taskrelevant movements are integrated into the learning process, thereby fostering generative learning.…”
Section: Facets Of Haptic Explorationmentioning
confidence: 99%
“…Empirical research on finger tracing showed mixed results concerning the positive effect of tracing on cognitive load. While some studies failed to show a reduction in perceived cognitive load through tracing (Agostinho et al 2015;Ginns et al 2016;Korbach et al 2020;Macken and Ginns 2014), other studies found that tracing can have a positive effect on test item difficulty ratings, which can be interpreted as a measurement of intrinsic cognitive load (Du and Zhang 2019;Hu et al 2015;Yeo and Tzeng 2019). In a recent study, it was found that primary school students who traced while studying learning material about the water cycle showed lower extraneous-but not intrinsic-cognitive load than students who were not allowed to trace (Tang et al 2019).…”
Section: Processing In Working Memory and Storage In Long-term Memorymentioning
confidence: 99%